Discrete Approach in Innovation Test Assessment of Student Arabic Reading Ability - Kadar, Haerani; Pratama, Budi; Dian, Zidna Ilma; Riswar, Hanan (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to innovate the assessment of Arabic reading ability for grade 7 students at MTs N 3 Mataram using a discrete approach. This type of research is Research and Development (R&D) using the ADDIE development model. The research population comprises classes VII A, B, C, and D, with class VII C serving as the research sample, selected purposively. Data collection methods included observation, interviews, and documentation. The data sources for this research include field-collected data and previous literature. The data analysis technique for R&D research uses qualitative data analysis following Miles and Huberman, while quantitative data analysis employs descriptive statistical analysis. The results showed that of the 26 students, 5 (20%) could not read Arabic texts, 8 (30%) were still stammering, and 13 (50%) were fluent readers. Discrete tests are carried out in two types: the ability to read hiwar (dialogue) and qiro'ah (reading), with an assessment focusing on the accuracy of harakat, makharijul letters, interaction, courage, and fluency in reading. This approach allows for a more detailed assessment and helps the teacher design learning strategies that align with students' individual abilities.